PENGEMBANGAN MEDIA AUDIO VISUAL PADA MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MATA PELAJARAN GARDU INDUK (GI) KELAS XI TJTL SMK - Yosanda, Dwi Putri; ., Baharuddin (Universitas Negeri Medan, 2023)
Abstract This research aims to: (1) Find out how to develop audio visuals in the Discovery Learning Learning Model for the Main Substation (GI) Subject at SMK Negeri 1 Percut Sei Tuan. (2) Knowing the feasibility of Audio Visual in the Discovery Learning learning model developed for students of SMK Negeri 1 Percut Sei Tuan. (3) Knowing students' responses to Audio Visual in the Discovery Learning model developed for students of SMK Negeri 1 Percut Sei Tuan. This research will be tested involving class This type of research is Research and Development (R&D) with the ADDIE research model. The ADDIE research model includes 5 stages, namely first analysis which includes product needs analysis, second design, namely compiling an outline, layout and Audio Visual material, third development, namely developing a product that has been designed for validation in order to get input by media experts and material experts. The fourth implementation is implementing the product to get a response from users (Students) to the Audio Visual that has been developed. The fifth evaluation is evaluating Audio Visual based on several inputs from experts and user responses. The instruments used in this research were a validation questionnaire and a user response questionnaire. The results of this research are known: (1) This development research produces a product in the form of Audio Visual in the Discovery Learning learning model. (2) The feasibility of this Audio Visual was obtained from the results of material expert validation in the